High Altitude Hospitality - Joshi, Basant Prasad (Journal of Tourism and Hospitality Education, 2017)
Most of the books and journals of hospitality and tourism, generally talk about history, trends and components of hospitality as a newly emerging discipline but there are a few books could only make significant contribution on the prospects, challenges and opportunities for hospitality especially in high altitudes where the challenges are ample. People would basically be interested to travel to altitudes to crave the places of adventures specially trekking, hiking, mountaineering, rock climbing, snow skiing, etc. Providing hospitality in high altitudes is a very perplexing task where there is always a scarcity of man, material and management. Hochschild (2003) in his book The Managed Heart explains about the human factors that are important in providing hospitality services. The importance of feelings and its belongings on the offered services to the client and guests has a direct bearing on the overall experience and this experience is much important in high altitudes where the sentimental values are more important than the physical elements of a good service.Journal of Tourism and Hospitality EducationVol. 7, 2017, page : 62-82